(untitled) (International Journal of Engineering and Computer Science, 2014)
Paper includes the proper selection process of area for mobile computing parameter analysis. So there can be a process so that the site around and area is selected and then the features of mobile network are analyzed on the basis of recent applications. The features or parameters on the basis of Performance of GSM network can be as follows: Blocked Call Analysis, Drop Call Analysis, Speech Quality Parameters, and Speech Quality Analysis, Handover Analysis, Coverage Analysis, Quality of SFH & Non-SFH network, Drop Call Rate, Call setup success rate, Blocked Call Rate, Hopping C/I.